Modulation of Internal Tides by Turbulent Mixing in the South China Sea - Li, Bingtian; Du, Libin; Peng, Shiqiu; Yuan, Yibo; Meng, Xiangqian; Lv, Xianqing (Frontiers in Marine Science, 2021)
Modulations of internal tides (ITs) including the baroclinic tidal energy budget, the incoherency and the nonlinear interactions among different tidal components by turbulent mixing in the South China Sea (SCS) are investigated through numerical simulations. The baroclinic tidal energy budget can hardly be affected by the structure of mixing. Meanwhile change in the mixing intensity in a reasonable range also cannot obviously modulate the baroclinic tidal energy budget in the SCS. Comparing with the baroclinic energy budget, the influence on spatial distributions of conversion and dissipation is more evident when turbulent mixing changes. Turbulent mixing also modulates incoherency of ITs by changing the horizontal density in the ocean. The horizontal variation of density adds incoherence to ITs largely by affecting the internal tidal amplitudes. Furthermore, nonlinear interactions among different components of ITs are generally modulated by the mixing intensity, whereas variation of mixing structure can hardly influence the nonlinear interactions. Therefore, the diapycnal diffusivity can set to be horizontally and vertically homogeneous in most of the internal tidal simulations except for those in which the incoherency of ITs needs to be simulated. However, excessive strong mixing will destroy the stratification. Thus, the optimum range for IT simulations in the SCS is from O (10-5) to O (10-3) m2s-1.